2015
DOI: 10.1063/1.4929322
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the antiferroelectric phase during polarization cycling of an induced ferroelectric phase

Abstract: Articles you may be interested inAnomalous polarization in the antiferroelectric-ferroelectric phase coexistence state in PbZrO3-Bi(Mg1/2Ti1/2)O3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The AFE-FE interface returns to its original position while being slightly poked. After 1000 cycles, the AFE-FE interface seems to continue to shift upward AFE ceramics claimed that either the AFE or FE phase can be stabilized during cycling [14][15][16]. Microscopically, this may be manifested in the shift of the AFE-FE interface toward either direction.…”
Section: Resultsmentioning
confidence: 99%
“…The AFE-FE interface returns to its original position while being slightly poked. After 1000 cycles, the AFE-FE interface seems to continue to shift upward AFE ceramics claimed that either the AFE or FE phase can be stabilized during cycling [14][15][16]. Microscopically, this may be manifested in the shift of the AFE-FE interface toward either direction.…”
Section: Resultsmentioning
confidence: 99%
“…After 2.5 Â 10 6 cycles, the double loops almost become a slanted single loop with considerable P r and apparent coercive fields, suggesting the stabilization of the induced FE phase upon electric cycling. 32 The fatigue effect on the field-induced strain in PZ-L is shown in Fig. 5b.…”
Section: Fatigue Of the Afe Ceramicsmentioning
confidence: 99%
“…[15][16][17] The AFE-to-FE phase transition is a complex phenomenon, which includes structural phase transformations, unit cell volume changes, domain switching and texture formation. 5,[13][14][15][16][18][19][20][21][22] The AFE-to-FE transition has been reported using macroscopic studies, 12,[23][24][25] however microscopic studies to date are scarce. 5,[13][14][15][16][18][19][20][21][22] There is much that can be learned from studying the structural evolution at various fields before, during and after the AFE-to-FE phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, recent investigations have demonstrated that the AFE composition (Pb0.99Nb0.02[(Zr0.57Sn0.43)0.92Ti0.08]0.98O3) with a field assisted AFE-to-FE transition remains in a stable FE phase after the field is removed. 13 Furthermore, it is possible to induce the AFE phase from previously induced and poled FE phases by applying an electric field of reverse polarity. [15][16][17] The AFE-to-FE phase transition is a complex phenomenon, which includes structural phase transformations, unit cell volume changes, domain switching and texture formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation